Integral Sum 90

Calculus Level 4

Compute

0 1 ( n = 2 cos ( π n x ) n ) d x \int_0^1 \left(\sum _{n=2}^{\infty } \frac{\cos (\pi n x)}{n}\right) \, dx


The answer is 0.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

First Last
Jan 1, 2018

Moving the integral to the inside: 0 1 n = 2 cos ( π n x ) n d x = n = 2 0 1 cos ( π n x ) n d x = n = 2 sin ( n x ) n 2 sin ( n x ) is always 0 for integer n \displaystyle\int_0^1\sum_{n=2}^\infty\frac{\cos{(\pi n x)}}{n}dx=\sum_{n=2}^\infty\int_0^1\frac{\cos{(\pi n x)}}{n}dx=\sum_{n=2}^\infty\frac{\sin{(nx)}}{n^2}\quad\sin{(nx)}\text{ is always 0 for integer n}

n = 2 sin ( n x ) n 2 = 0 \displaystyle\sum_{n=2}^\infty\frac{\sin{(nx)}}{n^2}=0

The sum doesn't converge uniformly so how do you justify the change of sum and integral?

Markus Reibnegger - 3 years, 4 months ago

0 1 ( n = 2 C o s ( π n x ) n ) d x \int_0^1(\sum_{n=2}^{\infty}\frac {Cos(\pi nx)}{n})dx = l n ( S i n x ) = l n ( 2 ) n = 1 C o s ( 2 n x ) n ln(Sinx)=-ln(2)-\sum_{n=1}^{\infty}\frac {Cos (2nx)}{n} = 0 1 [ n = 2 C o s ( n π x n ] d x \int_0^1[\sum_{n=2}^{\infty}\frac {Cos(n\pi x}{n}]dx = 0 1 [ l n ( 2 ) l n ( S i n π 2 x ) C o s ( π x ) ] \int_0^1 [-ln (2)-ln (Sin\frac{\pi}{2}x)-Cos(\pi x)] = l n ( 2 ) 2 π 0 π 2 l n ( S i n x ) d x -ln (2)-\frac {2}{\pi}\int_0^{\frac {\pi}{2}}ln(Sinx)dx Now using Clausen function C l 2 ( z ) Cl_2 (z) C l 2 ( z ) : = 0 z l n ( 2 S i n t 2 ) d t Cl_2(z):=-\int_0^z ln(2Sin\frac {t}{2})dt = n = 1 S i n ( n z ) n 2 \sum_{n=1}^{\infty}\frac {Sin (nz)}{n^2} Integral can expressed as 1 2 C l 2 ( π ) π 2 l n ( 2 ) -\frac {1}{2}Cl_2(\pi)-\frac {\pi}{2}ln (2) . We can notice that the integral, C l 2 ( m , π ) = 0 Cl_2 (m,\pi)=0 where, m Z \forall m\in\mathbb {Z} due to the series representation.

= l n ( 2 ) 2 π 0 π 2 l n ( S i n x ) d x = l n ( 2 ) 2 π [ 1 2 C l 2 ( π ) π 2 l n ( 2 ) ] = 0 ln (2)\frac{2}{\pi}\int_0^{\frac {\pi}{2}}ln (Sinx)dx=-ln (2)-\frac {2}{\pi}[-\frac {1}{2}Cl_2 (\pi)-\frac {\pi}{2}ln (2)]=0

Pawan Goyal - 2 years, 1 month ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...